Jake Dunaetz: capstone - Dunaetz, Jake, artist (Colorado State University. Libraries, 2021)
The artist's statement: As a current graphic design student at Colorado State University, I am focusing on my growth not only as an artist but as a communicator as well. While developing as an artist by working towards my Bachelor of Fine Arts at Colorado State University, I have been working on rounding out my skills in the areas of design, artistry and communication. I have been a freelance illustrator with the Rocky Mountain Collegian producing illustrations to compliment the articles. In Addition, my time with COLAB: Lory student center Marketing, I have gained a lot of knowledge of the inner workings of the professional art world, and I have proven I can produce art on a professional level. The most important lesson I have learned from my position is how to manage time and being able to hold myself accountable. Especially during the pandemic, as a freelance illustrator, I have had no face-to-face interaction with my bosses. Through my volunteer work, managerial positions and customer service, I have learned the necessary tools to communicate with not only my co-workers but with clients as well. My passion for exploration and discovery is the driving force behind my art and life. The pursuit of new experiences and connecting to the world around me has always been a focus of mine. Traveling has always been a large part of my life. Through my adventures to locations like Beijing, Tokyo and Barcelona, I can explore and be immersed in cultures that are drastically different from mine, allowing me to learn and grow in completely new ways. I attain inspiration from cultures other than my own, giving me new perspectives through mediums such as architecture, advertising, and landscapes. These contribute to my ability to expand my knowledge and techniques for communicating through my art.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design